2019
DOI: 10.3389/fmicb.2019.00083
|View full text |Cite
|
Sign up to set email alerts
|

milR4 and milR16 Mediated Fruiting Body Development in the Medicinal Fungus Cordyceps militaris

Abstract: Cordyceps militaris readily performs sexual reproduction, thus providing a remarkably rich model for understanding the processes involved in sexual development. It could regulate expression of human genes by diet-derived miRNA-like RNAs (milRNAs). However, the study of miRNAs in C. militaris has been limited. In the present study, genes encoding Dicers, Argonautes, and RNA-dependent RNA polymerases were identified. Illumina deep sequencing was performed to characterize the milRNAs in C. militaris at asexual an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Argonaute-family proteins were developmentally regulated in all nine species, suggesting RNA interference as a widespread regulatory mechanism of CM morphogenesis, consistent with recent reports on individual species ( Lau et al. 2018 ; Shao et al. 2019 ).…”
Section: Resultssupporting
confidence: 89%
“…Argonaute-family proteins were developmentally regulated in all nine species, suggesting RNA interference as a widespread regulatory mechanism of CM morphogenesis, consistent with recent reports on individual species ( Lau et al. 2018 ; Shao et al. 2019 ).…”
Section: Resultssupporting
confidence: 89%
“…Total RNA was extracted at different asexual developmental stages of S. sanghuang, i.e., 10 days old (M10d) and 20 days old (M20d), as well as from different sexual developmental stages, i.e., one year old (OY) and three year old (TY). The cDNA was synthesized and quantitative PCR was performed as reported previously (Shao et al, 2019). qPCR amplification was performed with a SYBR Green kit (Takara) and Bio-Rad CFX96TM system (Hercules, CA, United States).…”
Section: Quantitative Pcr (Qpcr)mentioning
confidence: 99%
“…With the development of high-throughput sequencing technology, the existence of miRNA or milRNAs in O. sinensis have already been shown. Here, 106 novel milRNAs were identi ed from our sRNA-Seq data, which greatly enrich the miRNA database of this Cordyceps fungi 16,18 . miRNAs regulate gene expression mainly by promoting cleavage of the target mRNAs or by regulating TFs; therefore, DEM-DEG target gene relationship pairs can re ect the regulatory function of milRNAs more accurately.…”
Section: Discussionmentioning
confidence: 98%
“…The small RNA-mediated RNA interference mechanism plays an important role in the ne-tuning of the transcriptome during ascospore formation in Fusarium graminearum 17 . In Cordyceps militaris, disruption and overexpression of candidates milR4 and milR16 con rmed that milRNAs in C. militaris regulate fruiting body formation 18 . These studies suggested that milRNAs may play important roles in the regulation of development in O. sinensis.…”
Section: Development Of Fruiting Bodies Inside Ascomycetes Is a Complmentioning
confidence: 92%